Human Resource Development Competence Motivation and Employee Performance: Pengembangan Sumber Daya Manusia, Kompetensi, Motivasi, dan Kinerja Karyawan - Tia Aulia; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Human resources are a strategic element in organizational sustainability and performance achievement. Specific Background PT. BPR Arta Seruni faces challenges related to employee performance amid limited human resource development, varying competency levels, and insufficient motivation. Knowledge Gap Previous studies show inconsistent findings regarding the role of human resource development, competency, and motivation in explaining employee performance. Aims This study aims to examine the partial and simultaneous relationships between human resource development, human resource competency, and motivation with employee performance. Results Using quantitative explanatory research with total sampling of 60 employees and multiple linear regression analysis, the findings show that human resource development, competency, and motivation are each statistically significant, both individually and simultaneously, in relation to employee performance. Novelty This study provides empirical evidence from a regional banking institution by integrating three key human resource variables within one analytical model. Implications The findings offer practical insights for organizational management in designing structured human resource development, competency alignment, and motivational strategies to support employee performance. Keywords: Human Resource Development, Human Resource Competency, Motivation, Employee Performance, Banking Organization Key Findings Highlights: Training and development practices are statistically associated with employee work outcomes. Skill and knowledge alignment corresponds with measurable performance levels. Work motivation demonstrates a consistent statistical relationship with task achievement.